Prophetic Communication: Transcendental Dimension In Islamic Philanthropy Messages - Rakhmawati, Yuliana (Institut Agama Islam Negeri Madura, 2020)
Indonesia Islamic philanthropy had been growing tremendously. Trends in institutions platforms in managing Islamic philanthropy brought the divergence of channel message distribution. Those institutions made convergence interdisciplinary innovation. Islamic philanthropy institutions obligate to distribute the message in an ethical manner. They employed prophetic communication values in engaging the public sphere with persuasive communication commonly. Prophetic communication design is a custom to promote transcendental dimension of contemporary communication praxis. The prophetic term uses the cognition proximity design refers to Prophet Muhammad as a role model. This research was conducted to get an overview of the prophetic communication representation in the Islamic philanthropic messages distribution. Analytical techniques use qualitative document analysis. The subject in this research is the display of text on the site of Islamic philanthropic foundations official website Rumah Zakat, Yayasan Dana Al-Falah, and Lembaga Manajemen Infaq. The theme categories enrich found with selective coding. The results of the analysis are discussed using the concepts of prophetic communication, message production theory, goal-plan-action theory, action-making theory, and cognitive dissonance theory. For further research could obtain from the communication management of more specific philanthropic objects.